Childhood health and educational investment under risk - Neha Kumra (IZA Journal of Labor & Development, 2017)
A huge literature shows that childhood health and educational attainment are highly correlated. However, estimates for the effect of childhood health on educational attainment under risk generally confound the effect of liquidity constraints and of lack of insurance against risk. It is unclear whether the correlation between health and education under uninsured risk would remain if the capital markets were perfect and household faced no liquidity constraints. This paper fills in this lacuna in the literature. We develop a two period model of investment in education when future labor earnings are stochastically dependent on current investments in schooling and health. It is found that when there is uninsured risk, then parental investment in a child's education will be inefficient even in the presence of perfect capital markets. Under certain assumptions, there will be a positive correlation between childhood health and educational investment. Health inequalities will translate into educational inequalities in an environment of uninsured risk. We are able to show that when perfect insurance markets are present, investments in child health and schooling will be optimal. From the policy perspective, this argues for the development of insurance markets. The results also suggest that policy interventions that target higher levels of educational investment among the population need to account for the effect of childhood differences in health.
Keywords: O12; O16; O20; 330; Kinder; Gesundheit; Bildungsniveau; Bildungsfinanzierung; Investitionsentscheidung unter Unsicherheit; Privater Haushalt; Entwicklungsländer